Interactions between stock, bond and housing markets - Roberto Dieci; Noemi Schmitt; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2018)
We develop a model in which investors can participate in stock, bond and housing markets. Investors' market entry decisions are subject to herding effects and depend on the markets' price trends and on their mispricings. The dynamics of our model is governed by a four-dimensional nonlinear map and its unique inner steady state is characterized by standard present-value relations between dividends, rents and the bond rate. Amongst other things, we show that endogenous stock and housing market dynamics emerge, countercyclical to each other, if investors react strongly to the markets' price trends. Such a cross feedback reflects investors' tendency to transfer their enthusiasm from one speculative market to another.
Keywords: D84; G12; R21; 330; stock markets; housing markets; bond markets; bounded rationality; market interactions; nonlinear dynamics